Digital Sanskrit Buddhist Canon : saṅgaṇakīkṛtam bauddhasaṃskṛtatripiṭakam - Lancaster, Lewis R. (2004)
[Dt.:] Die University of the West und das Nagarjuna Institute of Exact Methods (NIEM) haben eine Volltextdatenbank angelegt, die den Zugang zu buddhistischen Texten in Sanskrit ermöglicht. Neben einem originalsprachlichen Zugang in Devanagari-Schrift gibt es auch einen für eine Transliteration in lateinischen Buchstaben. Enthalten sind verschiedene Textformen wie Sūtras, Śāstras und Stotras. Das Projekt startete 2003 und endete in der ersten Projektphase 2004 mit der Eingabe von 50 Mahāyāna sūtras. Seit 2005 werden ca. 100 śāstras digitalisiert und online zugänglich gemacht werden. Geleitet wird das Projekt von Lewis R. Lancaster. - [Engl.:] The University of the West and Nagarjuna Institute of Exact Methods (NIEM) have jointly launched the Digital Sanskrit Buddhist Canon Website for the benefit of the scholastic world. The goal is to promote research into the vast Sanskrit Buddhist Canon. The scriptures and treatises which make up this canon encompass thousands of printed pages. Electronic access to Sanskrit Buddhist texts, with its profound possibilities for enhancing the depth, scope and subtlety of research, has been a desideratum of the field for some time. In 2003, the University of the West, guided by the initiative of Prof. Lewis Lancaster, began the Sanskrit Buddhist Canon Project (SBCP). The initial grant, covering the input of 50 Mahayana sutras, was completed in 2004. The second phase, in 2005, covers the input of about 100 Shastra titles. The input of Shastras comprising the works of Acarya Nagarjuna, Arya Deva, Asanga, and Vasubandhu has already commenced, and will be completed by the end of 2006-7.